Interleukin‐2 gene polymorphism in Turkish patients with Behçet's disease and its association with ocular involvement. (21st January 2013) - Yücel, A.; Dilek, K.; Saba, D.; Özçimen, A. A.; Yurtkuran, M.; Oral, H. B.
Summary: Behçet's disease (BD) is a chronic immune‐mediated systemic disease, characterized by oral and genital lesions and ocular inflammation. Several cytokine genes may play crucial roles in host susceptibility to BD, because the cytokine production capacity varies among individuals and depends on the cytokine gene polymorphisms. The association of the interleukin (IL)‐2 gene polymorphisms with the susceptibility to BD was investigated in this study. DNA samples were obtained from a Turkish population of 97 patients with BD and 76 healthy control subjects. Polymorphisms of IL‐2 gene at position −330 and +166 were determined using the polymerase chain reaction with sequence‐specific primers. In the patients with BD, there was a significantly increased frequency of IL‐2 −330 GT genotype. Interestingly, we demonstrated that the frequencies of IL‐2 −330 GT and IL‐2 + 166 GG genotypes were increased in BD patients with ocular involvement, whilst IL‐2 −330 TT genotype was significantly decreased. Also, analysis of allele frequency demonstrated that the presence of G allele at position +166 of IL‐2 seems to be a risk factor for ocular involvement. These results reveal that IL‐2 −330 GT genotype may be a susceptibility factor for BD, whereas IL‐2 −330 TT genotype seems to display a protective association with BD. Additionally, IL‐2 gene polymorphisms might be associated with ocular involvement in BD.